A study of the interplay effect in radiation therapy using a Monte-Carlo model. (July 2021) - Leste, Jeremy; Medjahed, Imene; Chauvin, Maxime; Younes, Tony; Vieillevigne, Laure; Ferrand, Regis; Franceries, Xavier; Bardies, Manuel; Simon, Luc
Highlights: Interplay effect is assessed with a Monte-Carlo model (GATE) of a Varian TrueBeam. Computed dose from the model is first confronted to measurements (moving platform). Using the model different parameters of the breathing motion are studied. An open-source package is proposed to the radiotherapy community. Abstract: Purpose: In modulated radiotherapy, breathing motion can lead to Interplay (IE) and Blurring (BE) effects that can modify the delivered dose. The aim of this work is to present the implementation, the validation and the use of an open-source Monte-Carlo (MC) model that computes the delivered dose including these motion effects. Methods: The MC model of the Varian TrueBeam was implemented using GATE. The dose delivered by different modulated plans is computed for several breathing patterns. A validation of these MC predictions is achieved by a comparison with measurements performed using a dedicated programmable motion platform, carrying a quality assurance phantom. A specific methodology was used to separate the IE and the BE. The influence of different motion parameters (period, amplitude, shape) and plan parameters (volume margin, dose per fraction) was also analyzed. Results: The MC model was validated against measurement performed with motion with a mean 3D global gamma index pass rate of 97.5% (3%/3 mm). A significant correlation is found between the IE and the period and the antero-posterior amplitude of the motion but not between the IE and the CTV margin or the shape of motion. The results showed that the IE increases D2% and decreases the D98% of CTV with mean values of +6.9% and −3.3% respectively. Conclusions: We validated the feasibility to assess the IE using a MC model. We found that the most important parameter is the number of breathing cycles that must be greater than 20 for one arc to limit the IE.